Gestational and Breastfeeding Low-Protein Intake on Blood Pressure, Kidney Structure, and Renal Function in Male Rat Offspring in Adulthood - Lamana, Gabriela Leme; Ferrari, Ana Leticia Luchiari; Gontijo, José Antonio Rocha; Boer, Patrícia Aline (Frontiers in Physiology, 2021)
Background. Our previous studies demonstrated that maternal protein-restricted (low protein, LP) 16-week-old offspring had pronounced nephron number reduction and arterial hypertension associated with an unchanged glomerular filtration rate. An enhanced glomerular area may be related to increased glomerular filtration and overflow, which accounts for glomerular filtration barrier breakdown and early glomerulosclerosis. The effect of protein restriction during gestational and breastfeeding periods is unknown. Method. In the present study, creatinine and lithium clearance, renal morphometry, immunoblotting, and immunohistochemistry analysis were performed to elucidate the functional and structural changes in 16- and 24-week-old LP offspring compared with age-matched regular protein intake (NP) progeny. Results. LP rats' progeny had significantly reduced birth weight, without previous catch-up growth phenomena, in parallel with a decreased adiposity index. Transforming growth factor-beta 1 (TGF-β1) glomerular expression was significantly enhanced in the LP group. Also, the LP offspring had a 38% lower nephron number and an increased glomerular volume. They also presented with a higher cardiac index and arterial blood pressure compared with age-matched NP offspring. The LP rats exhibited augmented Na+/K+-ATPase in the proximal segments, and NOS1 immunoreactivity in whole renal tissue was associated with sodium retention in the proximal nephron segments. We also found significantly enhanced collagen content associated with increased TGFβ1 and ZEB1/2 renal immunoreactivity in LP offspring compared with NP offspring. Increased hypertrophy markers in LP podocytes were associated with an amplified IL-6/STAT3 pathway activity. Conclusion. To our knowledge, these are the first data demonstrating renal functional and structural changes in protein restriction during gestation and lactation model of fetal programming. The fetal-programmed adult offspring showed pronounced structural glomerular disorders with an accentuated and advanced fibrosis stage, without a change in the glomerular filtration rate. These findings suggest that the glomerular enhanced TGF-β1 action may induce ZEB1/2 expression that may cause glomeruli epithelial-to-mesenchymal transition. In addition, decreased nephron number in the LP offspring with preserved glomerular function may be related to protective or even attenuate the activated IL-6/STAT3 pathway.